Reactions in ultra-small droplets by tip-assisted chemistry. Issue 78 (29th July 2016) - Guardingo, M.; Busqué, F.; Ruiz-Molina, D.
Abstract : In this feature article, we review the advances made in the deposition of femtolitre-sized droplets on surfaces using tip-assisted lithographic methods and their use as nanoreactors. Abstract : The confinement of chemical reactions within small droplets has received much attention in the last few years. This approach has been proved successful for the in-depth study of naturally occurring chemical processes as well as for the synthesis of different sets of nanomaterials with control over their size, shape and properties. Different approaches such as the use of self-contained structures or microfluidic generated droplets have been followed over the years with success. However, novel approaches have emerged during the last years based on the deposition of femtolitre-sized droplets on surfaces using tip-assisted lithographic methods. In this feature article, we review the advances made towards the use of these ultra-small droplets patterned on surfaces as confined nano-reactors.